5.5 SOCIAL AND PHILOSOPHICAL VIEWS OF AMIR TIMUR - 1. Salimov Bakhriddin Lutfullaevich. Professor at Tashkent State Transport University. 2. Maxmudov Shoxrux Zokir o‘g‘li. Student at Tashkent State Transport University. (Innovative technologies in construction Scientific Journal, 2024)
Аnnotation Amir Temur is also among the heads of state who raised the flag of justice high in his country. He is one of the few rulers who was able to ensure justice in his country, despite the fact that it was very big and vast. Among our ancestors, Amir Temur, the most powerful person in the field of state and politics, established laws and used them to manage the country.